1978
DOI: 10.1111/j.1365-2125.1978.tb01678.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance studies with antihistamines.

Abstract: 1Effect of four antihistamines, chlorpheniramine (4 mg), clemastine (1 mg), promethazine (10 mg) and terfenadine (60 mg), on visuo-motor coordination and on subjective assessments of performance and well-being were compared with placebo in six healthy females from 0.5-7.0 h after morning ingestion of each drug. The study was double-blind, and the doses used were believed to be equally potent in their antihistaminic activity. 2 There was impaired performance 1.5 h (P< 0.01) after chlorpheniramine, 3.0 h (P< 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
37
4

Year Published

1986
1986
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(50 citation statements)
references
References 10 publications
9
37
4
Order By: Relevance
“…Promethazine has been shown to significantly impair psychomotor performance in several previous trials. Clarke and Nicholson (1978) demonstrated significant impairments in adaptive tracking 3 and 5 h post-drug, and non-significant impairments 1.5 and 7 h post-drug, following 10 mg oral promethazine. The Clarke and Nicholson (1978) study comprises the only other investigation into the psychomotor performance effects of promethazine for longer than 3 h; their time course data closely matches the present findings (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Promethazine has been shown to significantly impair psychomotor performance in several previous trials. Clarke and Nicholson (1978) demonstrated significant impairments in adaptive tracking 3 and 5 h post-drug, and non-significant impairments 1.5 and 7 h post-drug, following 10 mg oral promethazine. The Clarke and Nicholson (1978) study comprises the only other investigation into the psychomotor performance effects of promethazine for longer than 3 h; their time course data closely matches the present findings (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Parenteral promethazine comprises a standard treatment for personnel already vomiting, although the consequent sedation is marked (McMurray 1973;Hordinsky et al 1982). Oral promethazine significantly impairs psychomotor skills such as hand-eye coordination and adaptive tracking (Molson et al 1966;Large et al 1971;Clarke and Nicholson 1978), reduces critical flicker fusion threshold (Turner 1968;Hedges et al 1971), and leads to lowered feelings of alertness (Hedges et al 1971;Large et al 1971). The effects of oral promethazine upon information processing and cognitive skills to not seem to have been investigated, although parenteral promethazine impairs information processing (Hordinsky et al 1982).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have shown that single oral doses of 4 mg chlorpheniramine produced significant performance impairment, which was most pronounced shortly after t max (Kamei et al, 2003;Witek et al, 1995). Yet, in a third study performance was significantly impaired only at 1.5 h after drug administration (Clarke and Nicholson, 1978). On the basis of these results it was decided to measure the effects of dexchlorpheniramine at both times reported for peak impairment that is between 1.5 and 2.5 h and between 3.5 and 4.5 h after administration.…”
Section: Introductionmentioning
confidence: 96%
“…So far, however, combinations of ethanol with the newer "non-sedative" antihistamines (terfenadine, astemizole, cetirizine, loratidine or ebastine) have not shown potentiation [12][13][14][15][16][17][18][19]. Yet it is important to evaluate the interaction of each new antihistamines with ethanol, since there is the possibility that this new drug, non-sedative by itself, will somehow potentiate with alcohol.…”
mentioning
confidence: 99%